Analysis of the Approaches to the Assessment of Regional Processes of Formation of Social and Economic Security - Chichkanov, Valeriy Petrovich; Belyaevskaya-Plotnik, Lyubov Alexandrovna (Economy of Regions, 2016)
The aim of the article is to study the paradigm of regional development, the importance and the need to integrate social components in the assessment of the level of socio-economic security of the region. The analysis of regional development theory shows that the evolution of the regions theory moves in the direction of increasing the role of the society and factors of economic development. This correlates with the concept of the present study which increases the role of the society from the previously adopted subsystem in the economic security system to the equivalent of the social component in the socio-economic security. Often prevailing “economic” approach to solving the problems of social and economic security of a region is undoubtedly justified by the crucial importance of the economy for the territories. The threshold and critical values of certain indicators of socioeconomic security, beyond which destructive processes threaten the economy and the society, are analyzed. The authors note that achieving of the threshold values of security indicators demonstrates the need for immediate intervention by the authorities to overcome the undesirable tendencies. The basic methodological approaches to modeling and forecasting the socio-economic security of the region are systematized. The authors prove that it has to occur in an integrated manner, i.e. with the analysis and accounting of all aspects of the scope of the research, as well as in systematic manner taking into account the interrelations and interdependence of regional development. At the end of the research, a conclusion is formulated: the reasonable set of methods and opportunity to adapt them in short terms for new tasks in the conditions of a quickly changing environment of regions are necessary for the solution of various tasks of the analysis and the evaluation of socio-economic security.